2006
DOI: 10.1097/01.aog.0000198629.44186.c8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor Using a Foley Balloon, With and Without Extra-Amniotic Saline Infusion

Abstract: II-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…An infusion rate of 30 mL/h was used in our investigation and in the study by Guinn et al, 9 whereas an infusion rate of 40 mL/h was used in the Karjane et al trial. 10 There have been no randomized trials to date evaluating the effect of various extraamniotic saline infusion rates on the induction to delivery interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An infusion rate of 30 mL/h was used in our investigation and in the study by Guinn et al, 9 whereas an infusion rate of 40 mL/h was used in the Karjane et al trial. 10 There have been no randomized trials to date evaluating the effect of various extraamniotic saline infusion rates on the induction to delivery interval.…”
Section: Discussionmentioning
confidence: 99%
“…In the trial by Guinn et al, 9 no difference in the time from induction (Foley catheter insertion) to delivery, cesarean rate, or percentage of women who delivered within 24 hours was noted between the two arms. In contrast, Karjane et al, 10 in a larger trial of 142 women, found that the addition of extraamniotic saline infusion to a transcervical Foley catheter alone shortened the induction-to-vaginal-delivery interval. Because of these conflicting results, we conducted a large randomized clinical trial of transcervical Foley catheter compared with transcervical Foley catheter with extraamniotic saline infusion for labor induction and cervical ripening in women with unfavorable cervix.…”
mentioning
confidence: 87%
“…For the purpose of IOL in the third trimester, extra‐amniotic saline is infused through a transcervical catheter. Infusion rates can vary between 30 and 60 ml/hour . This results in stripping of the membranes with an increase in local PGs and other inflammatory mediators to induce labour …”
Section: Common Methods For Induction Of Labourmentioning
confidence: 99%
“…A Cochrane review concluded that there was insufficient evidence to support the use of EASI alone for IOL . EASI was found to reduce the induction delivery interval when used in association with the Foley catheter versus the Foley catheter itself; however, other studies found no benefit to using EASI in combination with Foley catheters …”
Section: Common Methods For Induction Of Labourmentioning
confidence: 99%
“…6 Trans cervical Foley ‫׳‬s catheter and extra amniotic saline infusion have been successfully used for cervical ripening and labour induction. 7 During the past 15 years the introduction of PGE1 (misoptrostol), a methyl analogue has been the major focus of attention for labour induction as it is cheaper and easy to store because of thermo stability. Currently only prostaglandin E2 (PGE2) is licensed for use for labour induction in case of viable pregnancies.…”
Section: Introductionmentioning
confidence: 99%